I felt completely broken, but I needed to be whole: the embodied and relational emotional experience of prison guards - Lima, Carlos Eduardo de (2024)
The prison environment is traditionally known to be challenging, complex, and hostile, not only for inmates but also for the professionals working in these institutions. In Brazil, the nature of prison work is marked by specificities such as overcrowding, the rise of criminal gangs operating inside and outside prisons, and the presence of power relations and political interests that turn these environments into true emotional arenas. One of the human figures inherent in prisons is the prison guards, whose work routine includes exposure to violence, high pressure, and the challenging task of practicing a stigmatized profession while simultaneously maintaining order and security. This context motivated the objective of this study, which is to understand how prison guards experience emotions at work and how they experience – in embodied ways – their relationship with their surroundings. The thesis was conducted through a phenomenological approach inspired by Maurice Merleau-Ponty. The research method used combined insider ethnography with Interpretative Phenomenological Analysis of twenty interviews conducted with twenty prison guards. Among the research results, it is highlighted that the emotional experience of prison guards is embodied and relational, as it is intertwined with other bodies, space, and time. The contributions of the research are twofold: first, I expand knowledge on emotion studies in organizational studies by theorizing its relational aspect. Secondly, I present an alternative way to explore emotions, whose approach broadens the possibility of understanding the experience with an enriched focus on cultural, material, and contextual dimensions.